Influence of current, spark on-time and off-time on electrode wear during EDM of mild steel - Khan, Ahsan Ali; Nazi Nadin, Mohd Faiz; Mohd Hambiyah, Mohammad Azhadi (International Islamic University Malaysia, 2011)
Abstract. The influence of current, spark-on time and off-time on electrode wear during EDM of mild steel with copper electrodes has been presented. As current increases, electrode wear also increases. This behaviour, as it is expected, because high current densities generate large amounts of heat, which rapidly overheats the electrode and causes it to wear. Electrode wear also increases with increase in spark on-time. The effect of the off-time on the electrode wear rate is inversely proportional to the electrode wear rate.